2021
DOI: 10.1111/conl.12800
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and protected areas: Impacts, conflicts, and possible management solutions

Abstract: During the first wave of the COVID-19 pandemic, management authorities of numerous Protected Areas (PAs) had to discourage visitors from accessing them in order to reduce the virus transmission rate and protect local communities. This resulted in social-ecological impacts and added another layer of complexity to managing PAs. This paper presents the results of a survey in Snowdonia National Park capturing the views of over 700 local residents on the impacts of COVID-19 restrictions and possible scenarios and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
2
24
0
2
Order By: Relevance
“…In line with the previous study by McGinlay et al (2020) , in which Jones is also a co-author, Jones et al (2021) suggested in his latest article to develop a mobile app for tourist guidance to avoid overcrowdedness in the protective areas. Many countries started lowering their fees for state-owned attractions to promote local tourism, but the same policy can impact their financial side.…”
Section: Resultssupporting
confidence: 61%
“…In line with the previous study by McGinlay et al (2020) , in which Jones is also a co-author, Jones et al (2021) suggested in his latest article to develop a mobile app for tourist guidance to avoid overcrowdedness in the protective areas. Many countries started lowering their fees for state-owned attractions to promote local tourism, but the same policy can impact their financial side.…”
Section: Resultssupporting
confidence: 61%
“…They can create specific zones such as playful visits or event spaces in which tourists can co-produce and co-create experiences more easily and based on their own intellectual and physical resources [55,97], whether the protected natural park is free or controlled. They can also manage overcrowding by restricting access to certain paths, the development of mobile applications to alert people to overcrowding and reporting irresponsible behavior [2,120].…”
Section: Sustainable and Sanitary Implications For Protected Natural Park Managersmentioning
confidence: 99%
“…The Covid-19 outbreak has had a very significant impact on tourism including important changes in mobility, social behavior, consumption habits, and leisure [1,2]. One of the consequences has been the rise of proximity tourism and domestic tourism [3] because tourists may consider nearby destinations more affordable, and, more importantly, less risky due to insecurity and uncertainty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, as open disputes have been hindered due to social distancing requirements (Smith et al 2021), many con icts may have taken the layer of 'underlying con icts' (Crespin and Simonetti 2021; Madden and McQuinn 2014;Zimmermann et al 2020), which makes capturing actors' perceptions more demanding. This adds to other con ict-inducing challenges to managers caused by the pandemic in PA socio-ecological systems, such as the reduction of nancial viability of PA stakeholders, an increase in their level of emotional stress (Smith et al 2021), higher pressure from domestic tourists on local PAs (Strzelecka et al 2021a), or limitations of the number of PA visitors due to pandemic restrictions (Jones et al 2021). Simultaneously, environmental policies worldwide, such as the latest EU 2030 Biodiversity Strategy (EC 2020), require increasing efforts to designate new PAs or expand existing ones.…”
Section: Introductionmentioning
confidence: 99%